2000
DOI: 10.1016/s0014-5793(00)01630-6
|View full text |Cite
|
Sign up to set email alerts
|

Protein disulfide isomerase mediates integrin‐dependent adhesion

Abstract: Cell adhesion is mediated by the integrin adhesion receptors. Receptor^ligand interaction involves conformational changes in the receptor, but the underlying mechanism remains unclear. Our earlier work implied a role for sulfhydryls in integrin response to ligand binding in the intact blood platelet. We now show that non-penetrating blockers of free sulfhydryls inhibit L L 1 and L L 3 integrin-mediated platelet adhesion regardless of the affinity state of the integrin. Removal of the inhibitors prior to adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
1
6

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 38 publications
4
129
1
6
Order By: Relevance
“…PDIs are required for cell viability (Ferrari and Soling, 1999) and differentiation (Ohtani et al, 1993), ion uptake (Honscha et al, 1993), regulating transcription (Markus and Benezra, 1999) and are found in the nucleus, cytoplasm, ER, mitochondria, and extracellular milieu (Couet et al, 1996;Lahav et al, 2000;Rigobello et al, 2001;Turano et al, 2002;Wilson et al, 1998). Recently, human PDI was found to bind signal peptide peptidase and unfold target proteins, leading to their dislocation from the ER to the cytoplasm and degradation by the ubiquitin-proteasome system, which is a process known as ER-associated degradation (ERAD) (Lee et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…PDIs are required for cell viability (Ferrari and Soling, 1999) and differentiation (Ohtani et al, 1993), ion uptake (Honscha et al, 1993), regulating transcription (Markus and Benezra, 1999) and are found in the nucleus, cytoplasm, ER, mitochondria, and extracellular milieu (Couet et al, 1996;Lahav et al, 2000;Rigobello et al, 2001;Turano et al, 2002;Wilson et al, 1998). Recently, human PDI was found to bind signal peptide peptidase and unfold target proteins, leading to their dislocation from the ER to the cytoplasm and degradation by the ubiquitin-proteasome system, which is a process known as ER-associated degradation (ERAD) (Lee et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…4), while sheep anti-FXIIIA2B2 antibody that does not interfere with PDI activity had no effect on adhesion. Moreover, the anti-PDI activity of rabbit anti FXIIA antibody reduced the adhesion of untreated platelets, probably by inhibiting surface-associated PDI on the platelets which is required for intact platelet adhesion (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, on the basis of our earlier findings that PDI plays a mediatory role in platelet adhesion [11][12][13] and that FXIIIA exerts PDI activity [10], we sought to examine the relative contributions of FXIII PDI or transglutaminase activity to platelet adhesion to fibrinogen.…”
Section: Thrombosis Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46][47] Some evidence suggests that PDI may also be localized to the cell membrane in tumor cells and there modulate integrin-dependent adhesion and sensitivity to chemotherapy. [48][49][50] To examine whether PDI is immunogenic in cancer patients, we established an ELISA with recombinant full-length human protein and evaluated sera from 46 metastatic melanoma, 22 metastatic non-small cell lung carcinoma, 2 metastatic ovarian carcinoma, and 12 acute myeloid leukemia patients who were enrolled on phase I clinical trials of vaccination with irradiated, autologous tumor cells engineered to secrete GM-CSF. We used a pan-human IgG secondary antibody to measure preferentially those isotypes dependent upon CD4 ϩ T-cell help for class switching.…”
Section: Pdi Is Immunogenic In Myeloid Leukemiamentioning
confidence: 99%